Recurrence Plot Based Damage Detection Method by Integrating Control Chart - Cheng Zhou; Weidong Zhang (Entropy, 2015)
Because of the importance of damage detection in manufacturing systems and other areas, many fault detection methods have been developed that are based on a vibration signal. Little work, however, has been reported in the literature on using a recurrence plot method to analyze the vibration signal for damage detection. In this paper, we develop a recurrence plot based fault detection method by integrating the statistical process control technique. The recurrence plots of the vibration signals are derived by using the recurrence plot (RP) method. Five types of features are extracted from the recurrence plots to quantify the vibration signals’ characteristic. Then, the  control chart, a multivariate statistical process control technique, is used to monitor these features. The  control chart technique, however, has the assumption that all the data should follow a normal distribution. The RP based  bootstrap control chart is proposed to estimate the control chart parameters. The performance of the proposed RP based  bootstrap control chart is evaluated by a simulation study and compared with other univariate bootstrap control charts based on recurrence plot features. A real case study of rolling element bearing fault detection demonstrates that the proposed fault detection method achieves a very good performance.